2018
DOI: 10.1371/journal.pone.0191368
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary protein intake and grip strength among adults aged 51 years and over: What We Eat in America, National Health and Nutrition Examination Survey 2011-2014

Abstract: IntroductionDistributing daily protein intake evenly across meals (∼25–30g/meal) has been suggested to improve muscle mass. The aim of this research is to examine the association between grip strength, total protein intake and its distribution across day’s meals in older adults.MethodsNationally representative dietary intake data of adults aged 51 years and older (n = 4,123) who participated in What We Eat in America, NHANES 2011–2014 were analyzed. Protein intake per day and per eating occasion (breakfast, lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
1
33
0
1
Order By: Relevance
“…Testing this rationale in 4123 adults >50 years old in the 2011–2014 National Health and Nutrition Examination Survey (NHANES), grip strength was positively associated with consumption of ≥25 g protein/meal on two or more eating occasions compared to only one eating occasion of the same amount. This relationship disappeared when adjusted for multiple covariates, including total daily protein intake, which was related with grip strength [ 47 ]. In contrast, in 1081 older adults (50–85 years) of the 1999–2002 NHANES, Loenneke et al (2016) found that participants consuming at least two meals containing 30–45 g protein/meal had the greatest leg lean mass and strength, and those consuming at least one meal/day of ≥30 g protein/meal had greater responses than those with no meal reaching the 30 g threshold [ 48 ].…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%
“…Testing this rationale in 4123 adults >50 years old in the 2011–2014 National Health and Nutrition Examination Survey (NHANES), grip strength was positively associated with consumption of ≥25 g protein/meal on two or more eating occasions compared to only one eating occasion of the same amount. This relationship disappeared when adjusted for multiple covariates, including total daily protein intake, which was related with grip strength [ 47 ]. In contrast, in 1081 older adults (50–85 years) of the 1999–2002 NHANES, Loenneke et al (2016) found that participants consuming at least two meals containing 30–45 g protein/meal had the greatest leg lean mass and strength, and those consuming at least one meal/day of ≥30 g protein/meal had greater responses than those with no meal reaching the 30 g threshold [ 48 ].…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%
“…In several previous studies showing an association between protein intake and muscle mass and function, protein intake was assessed by 24-h dietary recalls or food records on a maximum of three days [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. These studies used the mean protein intake for the analysis and did not take potential variations in protein intake across the week into account.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a randomized crossover study by Mamerow et al demonstrated that, despite a similar daily protein intake (~1.2 g/kg), an even distribution of daily protein intake significantly improved (~25%) MPS rates over 24 h when compared with a skewed protein intake [ 66 ]. To add further complexity, analysis of NHANES 2011–2014 data ( n = 4123, 51+ years old) showed a positive association between higher daily protein intake and grip strength in women but not men [ 67 ], which may indicate the presence of sex-based differences that warrant further study. A recent meta-analysis explored the influence of protein/amino acid supplementation on skeletal muscle mass and strength in older adults in the absence of an exercise intervention [ 68 ] and reported that protein/amino acid supplementation alone is unable to increase skeletal muscle mass or strength [ 68 ].…”
Section: The Importance Of Protein Intakementioning
confidence: 99%